Microwave hybrid heating as an alternative method for soldering—A brief review - N. M., Maliessa; S. R. A., Idris (Springer, 2023)
The paper reviews the Microwave Hybrid Heating (MHH) method as well as the effect of MHH towards the interfacial reaction and the shear strength at the solder/Cu joint. Previously, reflow soldering process was performed to solder electronic component. Due to its high defect rate, processing time and energy consumption, MHH method are getting more attention among electronics manufacturers to perform industrial process as it is beneficial in modern microtechnology. MHH method has faster heating rate, improve heating uniformity, reduces the chance of thermal runaway, reduce processing temperature, and reduce hazards to human and environment. This approach has proven to yield scallop-like and angular trapezoid structure of Cu6Sn5 and Cu3Sn in the intermetallic compound (IMC). The IMC thickness shows a competitive result (5.337μm and 5.717μm) compared to reflow soldering. However, not many studies were done on the shear strength of the solder joint.